Accurate parametrized variational calculations of the molecular electronic polarizability by NDDO-based methods - Schürer, Gudrun; Gedeck, Peter; Gottschalk, Maik; Clark, Timothy (International Journal of Quantum Chemistry, 1999)
The variational method for the calculation of the electronic polarizability of molecules within the NDDO-based semiempirical MO methods MNDO, AM1, and PM3 was parametrized to improve its accuracy. A training set of 156 compounds was used to fit 34 parameters simultaneously for 12 elements using a simplex optimization. The resulting parameters were tested for a test set of 83 molecules and the calculated polarizabilities compared with the experimental data. For AM1, the RMS deviation between experimental and calculated polarizabilities was reduced from 2.99 (using the original variational treatment) to 0.70 Angstrom(3) for the test set and from 2.81 to 0.40 Angstrom(3) for the training set. MNDO and PM3 gave similar improvements. (C) 1999 John Wiley & Sons, Inc. Int J Quant Chem 75: 17-31, 1999.
Keywords: polarizability; MNDO; AM1; PM3; NDDO